2018
DOI: 10.11646/zootaxa.4496.1.16
|View full text |Cite
|
Sign up to set email alerts
|

Comparative studies on reproductive traits of natural populations of Eisenia andrei Bouché, 1972 from Zagros Mountain, Iran (Annelida: Oligochaeta)

Abstract: Comparative studies were carried out on growth and reproduction patterns of eight populations of Eisenia andrei (Bouché, 1972) from different parts of western Iran along the Zagros Mountains, considered to lie within the natural range of this species. Parameters were gain in body weight, number of cocoon production, hatching success, number of hatchlings, hatchlings growth and survival. There were significant differences in mean numbers of viable cocoons, incubation time, reproductive rate, growth rate and fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Untill now, 35 species of Oligochaetes have been identified from different regions of Iran ( Ezzatpanah et al, 2010 ; Mirmonsef et al, 2011 ; Jabłońska and Pešić, 2014 ; Nazarhaghighi et al, 2014 ; Sanchooli et al, 2019 ; Latif et al, 2020 ). Some molecular surveys have been conducted to clarify whether these species are native or exotic ( Latif et al, 2018 ; Bozorgi et al, 2019 ). Recently, Javidkar et al (2020) reported a non-native Oligochaete Eiseniella tetraedra (Savigny, 1826) from two protected rivers in the southern Alborz Mountains.…”
Section: Introductionmentioning
confidence: 99%
“…Untill now, 35 species of Oligochaetes have been identified from different regions of Iran ( Ezzatpanah et al, 2010 ; Mirmonsef et al, 2011 ; Jabłońska and Pešić, 2014 ; Nazarhaghighi et al, 2014 ; Sanchooli et al, 2019 ; Latif et al, 2020 ). Some molecular surveys have been conducted to clarify whether these species are native or exotic ( Latif et al, 2018 ; Bozorgi et al, 2019 ). Recently, Javidkar et al (2020) reported a non-native Oligochaete Eiseniella tetraedra (Savigny, 1826) from two protected rivers in the southern Alborz Mountains.…”
Section: Introductionmentioning
confidence: 99%